Characterization of Hungarian touristical turnover 2006-2009 – focus on health tourism - Kalmár, Katalin (Acta Agraria Debreceniensis, 2012)
Tourism is one of the biggest and mostly increasing branch all over the world. Since it is getting more and more significant in Hungary as well in this article I analyze the turnover of Hungarian tourism on the basis of guest nights spent on commercial lodgings. I examine its changes in time and its territorial spreading. Finally I explore the health touristic volume, because it is one of the most important touristic product of Hungary and the North Plain Region and the infrastructure based upon preserves unique opportunities both for health and wellness tourism.